2019
DOI: 10.1111/jcpe.13067
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontal disease and preterm prelabour rupture of membranes

Abstract: Objective Periodontal disease is a possible contributing factor to preterm delivery. The aim of this study was to compare the periodontal status of women with preterm prelabour rupture of membranes (PPROM) and women with uncomplicated singleton pregnancies. Patients and Methods Seventy‐eight women with PPROM at gestational ages between 24 + 0 and 36 + 6 weeks and 77 healthy women with uncomplicated pregnancies, matched for gestational age at sampling without preterm birth, were included in this study. All wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Apart from the effect of hormonal changes, it is increasingly acknowledged[ 18 19 20 ] that other factors such as poor oral hygiene, lack of access to dental care, and low knowledge levels about proper oral hygiene maintenance affirmed to worsened periodontal condition during pregnancy. Further, more recent studies[ 21 22 23 ] indicated these oral alterations have the potential to affect pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the effect of hormonal changes, it is increasingly acknowledged[ 18 19 20 ] that other factors such as poor oral hygiene, lack of access to dental care, and low knowledge levels about proper oral hygiene maintenance affirmed to worsened periodontal condition during pregnancy. Further, more recent studies[ 21 22 23 ] indicated these oral alterations have the potential to affect pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The study found several factors correlating with periodontal health that can improve oral health, which in turn affect quality of life and reduce the risks for preterm birth [11,12]. As participation in medical dental screening was a main factor for achieving a healthier periodontal status, women need to be regularly counseled by gynecologists and dentists.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that maternal microbiota in other body sites such as oral (43)(44)(45)and gut (26,27) could affect the pregnancy processes and outcomes. The oral flora can be capable of oral-uterine transmission during pregnancy confirming the transferability of colonized flora.…”
Section: Discussionmentioning
confidence: 99%